Nondigestible Carbohydrates Affect Metabolic Health and Gut Microbiota in Overweight Adults after Weight Loss. Issue 7 (8th June 2020) - Johnstone, Alexandra M; Kelly, Jennifer; Ryan, Sheila; Romero-Gonzalez, Reyna; McKinnon, Hannah; Fyfe, Claire; Naslund, Erik; Lopez-Nicolas, Ruben; Bosscher, Douwina; Bonnema, Angela; Frontela-Saseta, Carmen; Ros-Berruezo, Gaspar; et al.
ABSTRACT: Background: The composition of diets consumed following weight loss (WL) can have a significant impact on satiety and metabolic health. Objective: This study was designed to test the effects of including a nondigestible carbohydrate to achieve weight maintenance (WM) following a period of WL. Methods: Nineteen volunteers [11 females and 8 males, aged 20–62 y; BMI (kg/m 2 ): 27–42] consumed a 3-d maintenance diet (15%:30%:55%), followed by a 21-d WL diet (WL; 30%:30%:40%), followed by 2 randomized 10-d WM diets (20%:30%:50% of energy from protein:fat:carbohydrate) containing either resistant starch type 3 (RS-WM; 22 or 26 g/d for females and males, respectively) or no RS (C-WM) in a within-subject crossover design without washout periods. The primary outcome, WM after WL, was analyzed by body weight. Secondary outcomes of fecal microbiota composition and microbial metabolite concentrations and gut hormones were analyzed in fecal samples and blood plasma, respectively. All outcomes were assessed at the end of each dietary period. Results: Body weight was similar after the RS-WM and C-WM diets (90.7 and 90.8 kg, respectively), with no difference in subjectively rated appetite. During the WL diet period plasma ghrelin increased by 36% ( P < 0.001), glucose-dependent insulinotropic polypeptide (GIP) decreased by 33% ( P < 0.001), and insulin decreased by 46% ( P < 0.001), but no significant differences were observed during the RS-WM and C-WM diet periods. Fasting blood glucose was lower after the RS-WM diet (5.59 ± 0.31 mmol/L) than after the C-WM diet [5.75 ± 0.49 mmol/L; P = 0.015; standard error of the difference between the means (SED): 0.09]. Dietary treatments influenced the fecal microbiota composition ( R 2 = 0.054, P = 0.031) but not diversity. Conclusions: The metabolic benefits, for overweight adults, from WL were maintained through a subsequent WM diet with higher total carbohydrate intake. Inclusion of resistant starch in the WM diet altered gut microbiota composition positively and resulted in lower fasting glucose compared with the control, with no apparent change in appetite. This trial was registered at clinicaltrials.gov as NCT01724411.